e-Learning campus in Malaysia: A case study on Multimedia University - Chong, Pei-Fen; Goh, Hong-Wee; Poon, Wai-Ching (2004)
This paper aims to discuss the development of e-learning in Malaysia, with Multimedia University (MMU) as the focal point. MMU, the first private university in Malaysia that has emphasized on the usage of Information Communication Technology (ICT) has made some revolutions in Malaysia’s education frontier. Using the state-of-the-art internet-based technologies and instructional facilities, the Internet Based Degree Programme (IBDP) provides flexibility to students to meet their education goals at their own pace and time. All the students need to do is access to a computer and the Internet to take advantage of the high quality, convenient, and cost-effective education and training provided by the MMU e-learning campus. In unison, e-management is widely employed via the in-house developed Integrated Computerized Education Management System (ICEMS) that promotes a paperless-administration environment and dissemination of information electronically between communities in both Cyberjaya campus and Malacca campus. The methodology of this paper will be a qualitative research, which will be based mostly on secondary data.